EVALUASI POLA PEWARISAN WARNA BUAH CABAI GENERASI F2 HASIL PERSILANGAN - Christina Astri Wirasti; Aziz Purwantoro (Program Studi Agroteknologi INSTIPER, 2017)
Chili is an agricultural commodity used in the field of food and industry, can also be used as an ornamental plant. As an ornamental plant, chilies are able to provide exciting new variations due to the striking color of the fruit. This study was conducted as an attempt to increase the variation genetic of chili especially related to fruit color character. In addition, it is expected to be used to study the pattern of inheritance of the fruit color of chili from the cross. The experiment was conducted in greenhouse of Faculty of Agriculture Gadjah Mada University and the screenhouse of Faculty of Agriculture Veteran National Development University. The research took place from November 2010 until in August 2013. Three introduction chilies were used in this experiment are Pepper Sweet Minimix, Orange Baby and Pepper Hot Razzamatazz and one local cayenne varieties (White Trisula). The results showed that the dominant red color to yellow, brown and orange, except on the crossing MX2 × RWT. The color of ripe fruit is controlled by two loci, although in some crosses shows cytoplasmic inheritance.